The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
14th WCCM-ECCOMAS Congress 2021
DOI: 10.23967/wccm-eccomas.2020.272
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Partitioned Approach On Fluid-Structure Interaction Simulations Using the Multiscale Universal Interface Coupling Library

Abstract: Fluid-Structure Interaction (FSI) is a phenomenon that appears in a wide range of scientific research and engineering applications at different spatial and temporal scales. There are many in-house/commercial solvers capable of modelling FSI, but high numerical robustness and high scalability codes are still in demand. In this study, a numerical framework for FSI simulations has been developed using a partitioned approach aimed at both high numerical robustness and good computational scalability. Open-source so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…1 shows the results of a 300-million-cell to 300-million-cell coupled case with a uniform 50/50 split of resources; this shows good parallel performance on up to 12,000 MPI tasks. The performance of the framework has also been demonstrated in our previous work (Liu et al, 2021b), which has shown acceptable scalability, with a parallel efficiency (i.e., speedup over number of MPI tasks) of 68% for 1,000 MPI tasks for FSI simulations using this framework.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…1 shows the results of a 300-million-cell to 300-million-cell coupled case with a uniform 50/50 split of resources; this shows good parallel performance on up to 12,000 MPI tasks. The performance of the framework has also been demonstrated in our previous work (Liu et al, 2021b), which has shown acceptable scalability, with a parallel efficiency (i.e., speedup over number of MPI tasks) of 68% for 1,000 MPI tasks for FSI simulations using this framework.…”
Section: Introductionmentioning
confidence: 68%
“…Systematic verifications and validations have been carried out for the coupling between OpenFOAM and FEniCS using the MUI library with a single-phase fluid solver in previous work (Liu et al, 2021b). It covers both two-dimensional (2-D) and three-dimensional (3-D) aero/hydroelastic cases within both laminar and turbulence regimes.…”
Section: Test Casesmentioning
confidence: 99%
“…Often, the categories of use cases are not strict. MUI, for example, has recently also been used for fluid-structure interaction 30 . At the same time, current work on preCICE aims towards certain multi-scale coupling patterns (cf.…”
Section: Amendments From Versionmentioning
confidence: 99%
“…The example is meant to serve as a first impression of how the preCICE API looks and how to use it along with deal.II. 30 code_aster adapter on GitHub: https://github.com/precice/code_aster-adapter, GPLv2…”
Section: Fenicsmentioning
confidence: 99%
“…The code is available on GitHub 30 under the GPLv2 license and can be easily extended by adding more coupling fields in adapter.py and providing their names as arguments to the method adapter.writeCouplingData().…”
Section: Code Astermentioning
confidence: 99%